MANAJEMEN SUMBER DAYA PENDIDIK DALAM MENINGKATKAN PROFESIONALISME PENDIDIK DI GUGUS SEKOLAH I KECAMATAN BANGIL KABUPATEN PASURUAN - Iis Megawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the management of educational human resources in enhancing teacher professionalism at SDN Dermo I and SDN Raci I, members of School Cluster I in Bangil District, Pasuruan Regency. Using a qualitative approach with a multi-site research design, data were collected through in-depth interviews, participant observation, and document analysis. Data were analyzed through data reduction, data display, and conclusion drawing, while validity was ensured through source and technique triangulation. The findings indicate that educational human resource management was implemented through systematic planning, continuous professional development, and regular evaluation. Planning involved identifying teachers’ needs and designing competency development programs aligned with school priorities and educational policies. Implementation included Teacher Working Groups (KKG), workshops, seminars, training, professional learning communities, and academic supervision, which contributed to improving teachers’ pedagogical, professional, social, and personal competencies. Evaluation was conducted through performance monitoring, instructional supervision, program reflection, and assessment of professional development outcomes. Supporting factors included principals’ commitment, a collaborative school culture, and school cluster support, while limited time, administrative workload, varying teacher motivation, and limited technology integration were identified as major challenges. The study concludes that systematic, collaborative, and sustainable educational human resource management effectively enhances teacher professionalism and supports improvements in the quality of learning in elementary schools.